Effectiveness of a counselling intervention implemented in antenatal setting for pregnant women facing domestic violence: a pre‐experimental study. (16th August 2019) - Arora, S; Deosthali, PB; Rege, S
Abstract : Objective: To assess the effectiveness of a counselling intervention in antenatal care settings for pregnant women who report domestic violence. Design: Pre‐experimental study with pretest‐posttest design. Settings: Two public hospitals in Mumbai, India. Sample: In all, 2778 pregnant women accessing antenatal care (ANC) in the hospitals from February to November 2016 were approached for study participation; 2515 women consented. These women were screened by trained counsellors for domestic violence during pregnancy (domestic violence during pregnancy). Domestic violence during pregnancy was reported by 16.2% (408) of women. Of these, 155 women sought counselling services. Post‐intervention analyses were carried out with 142 women at 6 weeks post‐delivery; 13 women were not contactable. Methods: The 442 women who reported domestic violence during pregnancy were provided a minimum of two counselling sessions by trained counsellors during their ANC visits. A counselling intake form was used to collect pre‐ and post‐intervention data. Main outcome measures: Prevalence of domestic violence during pregnancy, change in women's ability to cope, safety, and health. Results: Prevalence of domestic violence during pregnancy (16.1%) was comparable to those of common obstetric complications routinely screened for during ANC. In all, 60–65% women reported cognitive changes such as recognising impact of violence and need to speak out against it. In all, 50.7% women took action at the individual level to address domestic violence during pregnancy. This change was not statistically significant ( P ‐value 0.193). Of the women studied, 35.9% adopted at least one safety measure, and 84% of the women reported better health status post‐intervention. Conclusions: Routine enquiry and counselling for domestic violence during pregnancy are effective in improving women's ability to cope, safety, and health. Funding: This study was funded by The John D. and Catherine T. MacArthur Foundation. Tweetable abstract: Improving coping strategies, safety and health of pregnant women who reported domestic violence by providing counselling in antenatal care setting. Tweetable abstract: Improving coping strategies, safety, and health of pregnant women who reported domestic violence by providing counselling in antenatal care setting.